Communion: The Female Search for Love - bell hooks (New York William Morrow, 2003)
Intimate, revealing, provocative, Communion challenges every female to courageously claim the search for love as the heroic journey we must all choose to be truly free. In her trademark commanding and lucid language, hooks explores the ways ideas about women and love were changed by feminist movement, by women's full participation in the workforce, and by the culture of self-help. Communion is the heart-to-heart talk every woman -- mother, daughter, friend, and lover -- needs to have.
Keywords: Feminism; Relationships; Women; History; Nonfiction; Philosophy; Self Help; Love